Water exchange in the Baltic Sea: a historical view of research approaches from basin scales to submesoscale - Elken, Jüri; Omstedt, Anders (Frontiers in Earth Science, 2025)
At the beginning of the 20th century, Knudsen illustrated that the mean observed salinity of the Baltic Sea could be realistically estimated, assuming an inflow of saline Kattegat water equals the net freshwater supply, also called the Knudsen theorem. As given in the historical review, several studies have followed the approach of well-mixed boxes, including time variations and a division between different sub-basins in the Baltic Sea. The box concept was later developed into mechanistic models by resolving the vertical structure in each sub-basin and adding processes related to vertical mixing, strait flow dynamics, and exchange with the atmosphere. However, as with the box concept, each sub-basin was assumed to be horizontally homogeneous. Early on, it was clear that the Baltic Sea circulation was highly unsteady, with fronts and eddies at different scales, illustrating a typical marine turbulent flow with energy cascade from basin scale to mesoscale, submesoscale, and microscale, where the energy dissipates. Many observational and modeling studies addressing the three-dimensional structure were developed over the last half-century. The approach of mechanistic models is useful for interpreting large-scale effects of meso- and submesoscale processes and for climate and long-term studies. The submesoscale approaches, including in situ observations, remote sensing, and models resolving the three-dimensional structure, may guide parametrizations of exchange between and within the different sub-basins. Recent submesoscale studies suggest localized eddy-rich regions: Arkona Basin, Gulf of Finland, Irbe Strait, Åland Sea connections, and several coastal areas.